Food Processing and Phthalate Exposure: The Nutrition and Health Survey in Taiwan (1993–1996 and 2005–2008) - Huang, Yi-Chen; Huang, Pei-Ru; Lo, Yuan-Ting C.; Sun, Chien-Wen; Pan, Wen-Harn; Wang, Shu-Li; Huang, Han-Bin (Frontiers in Nutrition, 2021)
Background: Phthalates esters are widely used commercially and can leach from a food container or food packaging. Few studies have been conducted in Asia regarding food processed to varying levels and human phthalate exposure. This study aimed to evaluate the association between unprocessed and ultraprocessed food intake and urinary phthalate metabolite levels in a Taiwanese population. Methods: Participant data were extracted from the cross-sectional 1993–1996 and 2005–2008 Nutrition and Health Survey in Taiwan of those aged over 18 years, where urinary measures and one 24-h dietary recall were collected. Urinary concentrations of dimethyl phthalate, diethyl phthalate, dibutyl phthalate, butyl benzyl phthalate, and di(2-ethylhexyl) phthalate metabolites including monomethyl phthalate, monoethyl phthalate (MEP), monobutyl phthalate (MBP), monobenzyl phthalate, mono(2-ethylhexyl) phthalate, mono(2-ethyl-5-hydroxyhexyl) phthalate, and mono(2-ethyl-5-oxohexyl) phthalate were measured in spot urine samples. The NOVA food processing classification system was applied to unprocessed and ultraprocessed food. Generalized linear models were employed to examine the associations between the percentage quartiles (Qs) of unprocessed and ultraprocessed foods in the total weight of food and the urinary phthalate metabolites. Results: In adjusted models, participants with higher ultraprocessed intake had 65.7–75.1% higher urinary concentrations of MEP. The higher unprocessed food consumption was inversely associated with urinary concentrations of MEP and MBP (P for trend = 0.03). The percentage difference from Q4 for MEP in unprocessed food intake was −38.6 (95% confidence interval [CI]: −61.3, −2.59) and for MBP was −23.1 (95% CI: −38.5, −3.71) compared with Q1 after adjusted for covariates. Conclusion: Ultraprocessed food consumption was associated with increased urinary levels of certain phthalate metabolites. Conversely, consuming unprocessed food was associated with lower levels of these phthalate metabolites in the general Taiwanese population.